High-Power Pulse Generator for Cryogenic Devices; Instruments and Experimental Techniques; Vol. 40, № 4 - Uchaykin (Uchaikin) S. V. Sergey Victorovich (1997, 1997)
A pulse shaper generating -20 to 20 V voltage pulses and -4 to 4 A current pulses is described, which is intended for studies of the critical current of superconductors and heat-transfer processes in helium II. The minimum pulse duration is 50 ns, and the output voltage settling time is within a 0.025% accuracy in response to a 1 V step in the input voltage 0.9 s.